KONTRIBUSI KEKUATAN OTOT TUNGKAI DAN KELINCAHAN TERHADAP KEMAMPUAN MENGGIRING DALAM PERMAINAN SEPAKBOLA PADA MURID SDN 1 SEPAKAT 2018 - Jusran S; Sitti Maifa (STKIP Paris Barantai, 2018)
AbstractÂ This research is descriptive research type. This study aims to determine: (1) whether there is a contribution of leg muscle strength to the ability to lead to the game football students SDN 1 Sepakat. (2) is there any contribution of agility to the ability to lead to student soccer game SDN 1 Sepakat. (3) whether there is contribution of leg muscle strength and to ability to lead to student soccer game SDN 1 Sepakat.The population is a student of SDN 1 Sepakat. The sample used is SDN 1 Sepakat male students as many as 30 people. The technique of determining the sample is by random selection by drawing method (Simple Random Sampling). Data analysis technique used is descriptive analysis and inferential analysis through SPSS 20 program at significant level Î± 0,05.The results showed that; (1) there is a contribution of leg muscle strength to the ability to lead to the soccer game SDN 1 Sepakat students, by 26.5%, (2) there is agility contribution to the ability to lead to soccer game SDN 1 Sepakat, 45.0%, (3 ) there was a contribution of leg muscle strength and to the ability to lead to SDN 1 Sepakat pupil soccer game, 47.6% with F: 12.239 and sig (p) = 0,000.Â Keywords: leg muscle strength, agility, and dribbling